The curse of Camp Cold Lake - Stine, R. L. (New York : Scholastic, 1997)
Camp Cold Lake is no fun for Sarah, and she is not getting along with her bunkmates, but when she decides to pretend to drown, she realizes someone very strange has been watching her.
3.5
5-8
Keywords: Camps -- Juvenile fiction; Ghosts -- Juvenile fiction; Camps -- Fiction; Ghosts -- Fiction; Horror stories; Camps -- Fiction; Ghost stories; Horror fiction; Ghost stories